PERANAN KEPEMIMPINAN DAN MOTIVASI PADA ORGANISASI SERTA IMPLIKASINYA TERHADAP KINERJA ORGANISASI MELALUI KEPUASAN KERJA - Desta Rizky Kusuma (Universitas Ahmad Dahlan, 2018)
Job satisfaction to be one of the successful performance of the company. Leadership and motivation are factors that can determine a person's job satisfaction. This study wanted to examine the role of leadership in organizational performance. The purpose of this study was to test and prove that employee satisfaction is determined by the role of leadership and employee motivation. The results of this study are expected to provide an evaluation of the importance of the leadership role in creating job satisfaction can drive better organizational performance.